The systematization of Intervention as a Method of Investigation in Social Work. The Practical and Theoretical Importance of the Data Collection Phase in social intervention according to experience of the Family Support Program in Zaragoza, Spain - Esteban-Carbonell, Elisa; Del Olmo-Vicén, Nuria (Prospectiva. Revista de Trabajo Social e Intervención Social, 2021)
The main purpose of this work is to clarify, based on a case study, the limitations that the social scientist finds in Social Work research. Among the objectives of social services policies is the analysis of social   to detect situations of need. The systematization stands as a research methodology of the profession, given the privileged position of Social Work professionals as a thermometer of social reality.The objective of this article is to demonstrate the usefulness of the systematization of the practice as a method of research in social work; In particular, systematization focuses on a specific part of the practice: the collection of data from users, their codification and registration by the professionals of the social services centers.In conclusion, it has been observed that the systematization of the intervention process - in its initial phase of user data collection - allows not only to discern what type of data is useful and adequate to obtain positive results in the intervention, or what type of training should be given to social workers about the collection process; but also allow obtaining primary data, for the analysis of social reality, confirming the usefulness of the method itself.